2005
DOI: 10.1634/stemcells.2004-0330
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Derived from CD133‐Positive Cells in Mobilized Peripheral Blood and Cord Blood: Proliferation, Oct4 Expression, and Plasticity

Abstract: In this study, we used a common procedure to assess the potential of mobilized peripheral blood (MPB) and umbilical cord blood (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
266
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 403 publications
(287 citation statements)
references
References 42 publications
(54 reference statements)
11
266
2
6
Order By: Relevance
“…However, similar to MSCs, these cells were able to differentiate into adipocytes and osteocytes, suggesting that they are a higher cell lineage than cartilagecommitted progenitor cells, which are predetermined to form chondrocytes of elastic cartilage. In line with these expectations, CSPCs expressed CD44 and CD90, similar to MSCs, whereas they did not express the MSC markers CD133, CD140a, CD146, or CD271 (24,33,34). Thus, our isolated stem/progenitor cells are closely related to MSCs, yet are a distinct cartilage stem/ progenitor cell population.…”
Section: Discussionsupporting
confidence: 82%
“…However, similar to MSCs, these cells were able to differentiate into adipocytes and osteocytes, suggesting that they are a higher cell lineage than cartilagecommitted progenitor cells, which are predetermined to form chondrocytes of elastic cartilage. In line with these expectations, CSPCs expressed CD44 and CD90, similar to MSCs, whereas they did not express the MSC markers CD133, CD140a, CD146, or CD271 (24,33,34). Thus, our isolated stem/progenitor cells are closely related to MSCs, yet are a distinct cartilage stem/ progenitor cell population.…”
Section: Discussionsupporting
confidence: 82%
“…However, several differences between human and murine systems cannot be ignored; these differences include the expression patterns of surface antigens in MPCs, for instance (7,44,51,53). Moreover, human cells are difficult to transform in vitro, and the transformed cells of mice seem to produce a more aggressive tumor than those of hu-* Corresponding author.…”
mentioning
confidence: 99%
“…There have been many suggestions that MNCs might also be used for tissue regeneration because it was found that MSCs could be cultured and isolated from the MNC fractions of BM, CB, and mPB [7][8][9]. The effects of MSCs and MNCs have been compared in various experimental settings ( [19][20][21].…”
Section: Mscs Vs Mncs For Cell Therapymentioning
confidence: 99%